Graphene-based drug delivery systems - Bai, Reenu Geetha (2019)
Drug delivery is one of the prominent biomedical applications of graphene nanomaterials in the current scenario. The rapid growth in the graphene-based drug delivery systems showed the potential of this nanomaterial in the future health-care industry. The unique mono atomic planar structure and associated properties such as large surface area, chemical and mechanical stabilities, superb electrical conductivity, and good biocompatibility enabled the utility of these nanomaterials in medical applications. Advances in novel graphene-based nanotherapeutics, in preclinical investigations, show promise in using these cutting-edge therapeutic systems from bench to bedside in the near future. In this chapter, we have briefly discussed the recent advances in graphene-based drug delivery systems, in addition to the current status, future prospects, and challenges of these nanovehicles.